Transfer Pricing in the Oil and Gas Industry: Unique Challenges and Considerations - Babalola, Wasiu; Oyedokun, Godwin Emmanuel (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study critically examines the unique challenges and considerations associated with transfer pricing in the oil and gas industry. The primary aim is to explore the complexities surrounding intercompany transactions, valuation of commodities and intangibles, regulatory frameworks, and the implications of environmental and digital transformations. Employing a socio-legal study relying on qualitative and comparative methods and doctrinal methodology, the paper synthesizes insights from international guidelines (OECD, UN), national regulations, and industry-specific case studies, notably the Chevron-Australia dispute. It reveals that despite the availability of public commodity pricing, pricing intercompany crude oil and gas transfers remains complex due to quality differentials, contract structures, and regional benchmarks. The valuation of intangibles such as proprietary technology and seismic data is further complicated by the lack of comparables and centralized R&D structures. Regulatory divergence across jurisdictions, including formula-based systems like Brazil’s and hybrid models in Nigeria, increases compliance burdens for multinational enterprises (MNEs). Environmental and digital economy factors are also observed to be reshaping transfer pricing strategies, with carbon pricing and data-driven operations requiring new valuation models. The study concludes that a one-size-fits-all approach to transfer pricing is inadequate for the oil and gas sector. Instead, tailored strategies that reflect economic substance, greater adoption of Advance Pricing Agreements (APAs), and the use of technology for local compliance are vital for mitigating disputes, ensuring tax equity, and enhancing transparency in one of the world’s most strategically important industries.